Experimental Study on Sand Inrush Hazard of Water-Sand Two-Phase Flow in Broken Rock Mass - Junce Xu; Hai Pu; Jiarui Chen; Ziheng Sha (Geofluids)
In the western region of China, coal mining activities are prone to induce water and sand inrush disasters, which seriously threaten the safe production of the coal resources. In this paper, an experimental device was designed to simulate the process of water and sand inrush, and then, the control factors of the disasters in the broken rock mass in the goaf were investigated. Also, the seepage fracture channels in the broken rock mass were simplified by using the 3D printing technology, and the effects of fracture aperture and angle on the seepage characteristics of water-sand mixtures were analyzed. The experimental results showed that the porosity and skeleton structure of the broken rock mass were the key factors to control the water and sand inrush disasters. The smaller the initial porosity of the broken rock mass, the weaker its permeability, and the less probable to form a dominant channel for the water and sand inrush disasters. Conversely, the broken rock mass structure with larger size gradation was more likely to form the permeable channels, and the quality of the sand inrush was greater. In addition, it was also found that the angle of the fractures within the broken rock mass affected the seepage characteristics of water-sand mixture, and the permeability showed an exponential relationship with the fracture angle. Meanwhile, as the fracture aperture increased, the fracture angle generated greater influence on the permeability. Finally, we proposed the water and sand inrush prevention and control technology based on the experiment results. The results of this study can provide a reference for the control of water and sand inrush disasters in western China.